Sensory and Consumer Research for a Sustainable Food System - Knaapila, Antti (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book is a compilation of articles published in the Special Issue "Sensory and Consumer Research for a Sustainable Food System" of the journal Foods. The compilation includes 18 original research articles, 2 review articles, and 1 editorial. The articles show how sensory and consumer research can contribute to the development of a sustainable food system.